Beyond the Human: An Analysis of Posthumanist Themes and Ecological Consciousness in the Science Fiction of Dewi "Dee" Lestari - Abdurahman Abdurahman; Aom Thai; Siri Lek (Journal of Humanities Research Sustainability, 2025)
Background. This study examines posthumanist themes and ecological consciousness in the science fiction works of Dewi “Dee” Lestari, one of Indonesia’s most influential contemporary authors whose narratives frequently challenge anthropocentric worldviews. The background of this research lies in the growing global interest in posthumanist discourse, which critiques human-centered epistemologies and emphasizes the entanglement of humans, technology, and the natural environment. Purpose. The aim of this study is to analyze the narrative strategies, philosophical motifs, and ecological representations through which Dee constructs a posthumanist imaginary that destabilizes traditional boundaries between human and non-human agents. Method. The study employs a qualitative textual analysis method grounded in literary ecocriticism and posthumanist theory, drawing on close reading techniques and thematic mapping. Results. The results reveal that Dee’s narratives articulate a model of relational existence in which technology, consciousness, and ecological systems are interdependent rather than hierarchically ordered. Her work foregrounds ethical responsibility, cosmological humility, and the dissolution of rigid subject-object distinctions, offering a vision of scientific and spiritual evolution embedded within ecological awareness.   Conclusion. The study concludes that Dee’s science fiction significantly contributes to Indonesian literature by integrating posthumanist philosophy with ecological sensibility, encouraging readers to rethink the role of humans within a broader planetary network. This research highlights the relevance of Indonesian speculative fiction to global debates on ecological crisis and posthuman futures.